Corporate reporting, corporate governance mechanisms and tax aggressiveness: evidence from Indonesia / Ninuk Dewi Kesumaningrum ... [et al.] - Kesumaningrum, Ninuk Dewi; Bujang, Imbarine; Muda, Ruhaini; Mohamed, Norhayati (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This study aimed to empirically analyze the relationship between corporate reporting, both mandatory (financial reporting) and voluntary (Corporate Social Responsibility (CSR) disclosure) reporting, three corporate governance mechanisms (board size, independent board, and CEO duality), and tax aggressiveness in Indonesia. The study used a collected dataset of 121 public companies listed on the Indonesian stock exchange from 2016 to 2020. The data was collected from annual and sustainability reports published on the IDX and the company websites. The data was categorized based on classifications of non-financial industries because different characteristics and business cycles may influence tax aggressiveness decisions. Using the panel OLS approach, the research found that, in most industries, aggressive financial reporting positively relates, while CSR disclosures were negatively related to tax aggressiveness. The results also found that corporate governance mechanisms significantly related to tax aggressiveness in most industries. The findings suggest that board members, particularly independent boards with tax expertise and experience, can influence aggressive tax decisions. This study is the first to extract testing by industry classification, using mandatory financial reporting and voluntary CSR disclosures in Indonesia as indicators of corporate tax aggressiveness. The findings provide knowledge on company governance strategies to reduce aggressive tax actions.